China’s environmental “fee-to-tax” and foreign direct investment—An empirical study based on intensity difference-in-differences - Huang, Jiqiang; Li, Yanfeng (Frontiers in Environmental Science, 2023)
Foreign direct investment (FDI) plays an important role in deepening supply-side structural reform, promoting technological innovation, building a modern industrial system, and promoting high-quality development. The study uses balanced panel data of 287 prefectures in 30 of China’s provinces between 2003 and 2019 and constructs an intensity difference-in-differences model to test the impact of environmental "fee-to-Tax" on FDI. The empirical results show that: environmental "Fee-to-Tax" significantly boosts FDI, the findings hold through a series of robustness tests. The mechanism test finds that: environmental "fee-to-Tax" can promote high-quality economic development, and R&D innovation to increase the FDI. The heterogeneity test found that: environmental "Fee-to-Tax" mainly promoted the FDI in the east and central regions, not significantly in the western regions. This study can be of great significance for optimizing environmental tax policies and rationalizing the use of FDI to promote high-quality economic development.